2020
DOI: 10.1007/s11845-020-02407-z
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic variables as predictors of adverse outcome in SARS-CoV-2 infection: an Irish hospital experience

Abstract: Introduction Our hospital found itself at the epicentre of the Irish COVID-19 pandemic. We describe the organisational challenges faced in managing the surge and identified risk factors for mortality and ICU admission among hospitalised SARS-CoV-2-infected patients. Methods All hospitalised SARS-CoV-2 patients diagnosed between March 13 and May 1, 2020, were included. Demographic, referral, deprivation, ethnicity and clinical data were recorded. Multivariable regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Obesity has been identified as an important risk factor in other studies. ( 20 , 21 ) Our findings contrast with other studies reporting a stronger increased risk associated with chronic conditions, ( 22 ) and indeed we did find stronger associations between comorbidities and mortality prior to adjusting for age and frailty in the multivariable models; this is consistent with other studies where frailty has been considered. For example, a Swedish study also reported that frailty is the strongest predictive factor for mortality in older adults.…”
Section: Discussionsupporting
confidence: 77%
“…Obesity has been identified as an important risk factor in other studies. ( 20 , 21 ) Our findings contrast with other studies reporting a stronger increased risk associated with chronic conditions, ( 22 ) and indeed we did find stronger associations between comorbidities and mortality prior to adjusting for age and frailty in the multivariable models; this is consistent with other studies where frailty has been considered. For example, a Swedish study also reported that frailty is the strongest predictive factor for mortality in older adults.…”
Section: Discussionsupporting
confidence: 77%
“…A study conducted in Spain (Norman, 2021 ) underlines that ICU admission was more frequent in non-Europeans (OR 1.43, 95% CI [1.03–1.98]). Also, in another study from Ireland (Farrell, 2021 ), compared with White Irish patients, all other ethnic groups, including other White and BAME, had an approximately fourfold increased risk of ICU admittance after adjusting for age (adjusted HR=4.22, 95% CI [1.45–12.31] and 4.58, 95% CI [1.33, 15.84], respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies did not report an increased mortality risk for people with an ethnic minority background (Aw, 2020 ; Bannaga, 2020 ; Canevelli, 2020 ; Davies, 2021 ; Dennis, 2021 ; Farrell, 2021 ; Galloway, 2020 ; Giorgi-Rossi, 2020 ; Gopal-Rao, 2021 ; Guijarro, 2021 ; Ken-Dror, 2020 ; Kolhe, 2020 ; Livingston, 2020 ; Moody, 2021 ; Norman, 2021 ; Santorelli, 2020 ; Staines, 2021 ; Saban & Wilf-Miron, 2020 ; Thompson, 2020 ; Zakeri, 2020 ), and although Thomson et al (Thomson, 2020 ) found an association in the univariable analysis between Asian ethnicity and death (OR 2.57, 95% CI 1.02–6.57), in the multivariable model, this finding was not significant (Asian OR 2.94, 95% CI 0.94–9.78).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information regarding statistical analysis for individual studies as well as the raw data extracted from each study can be found in the supplement. Finally, most studies were peer reviewed and few included sensitivity analyses [16,37,40,[71][72][73][74] (Table 1).…”
Section: Plos Global Public Health Statistics Only and Included 71 Mo...mentioning
confidence: 99%